moral integrity Among Kindergarten Teachers (Journal of the College of Basic Education, 2023)
The current research aimed to know the moral integrity of kindergarten teachers, and the researcher followed the descriptive and correlative approach in her research. The behavioral component of moral discrimination, the cognitive component of moral discrimination, the emotional component of fixed behavior, the behavioral component of fixed behavior, the cognitive component of fixed behavior, the emotional component of general justification, the behavioral component of general justification, the cognitive component of general justification), the researcher verified the apparent validity of the integrity scale. The morality and consistency of its paragraphs, and its stability was calculated by the re-test method, as the transmission coefficient reached (0.94) and the Alpha Cronbach method, as the reliability coefficient reached (0.98). ), and the sample was chosen in a simple random way, and the research data was processed by statistical means that fit with the nature and objectives of the current research. Ele is:Median , Standard DeviationPearson Correlation CoefficientCronbach's alphaT-testT-test for a Single SampleT-test for a Correlation CoefficientThe researcher reached the following results:-The kindergarten teachers have moral integrity, as the results came with an arithmetic mean higher than the hypothetical average